Manfred Max Neef and the environmental revolution for Latin America, 1932-2019 (in memoriam) - Valenzuela-Van Treek, Esteban; Ostoic-Marroquín, Zoran; González-González, Jaime (Iberoamerican Journal of Development Studies, 2021)
With the article, it is offered a tribute to the work of Manfred Max Neef, Chilean intellectual, politician, ecologist and economist, Alternative Nobel Prize winner in Economics, a pioneer in ecological criticism of both productivism and extractivism in Latin America. The methodology used in this work is based on the review of the main books published by the author, such as Barefoot Economy (1982), Development on a Human Scale (1986), The Lost Dimension (2007), and The Unmasked Economy (2014). It is held as an assumption that Max Neef’s work fits into a Latin American theoretical body, which breaks intellectually with macroeconomic models, be they developmentalist or neoliberal in nature. The originality of his contribution is in the defense of the ecological foundations for human development at a local scale.
Keywords: Manfred Max Neef; economy; ecology; development; Latin America